1981
DOI: 10.1021/bk-1981-0161.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Curium—Americium Oxide Microspheres by Resin-Bead Loading

Abstract: A resin-bead loading and calcination technique developed at the Transuranium Processing Plant (TRU) of the Oak Ridge National Laboratory (ORNL) is used routinely for producing uniform particles of curium-americium oxide in the size range desired for the fabrication of targets for irradiation in the High Flux Isotope Reactor (HFIR). TRU is the storage, production, and distribution center for the heavy-element research program of the U. S. Department of Energy. Target rods are remotely fabricated at TRU, irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…The decomposition process and the results of this research were anticipated from documentation [1,4,7] and from the DGA/TGA results shown in Fig. 14.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The decomposition process and the results of this research were anticipated from documentation [1,4,7] and from the DGA/TGA results shown in Fig. 14.…”
Section: Discussionmentioning
confidence: 61%
“…Drying helped provide more uniform gas flow and kept the resin from lifting out of the tube during subsequent steps. With the assistance of purge gases, the majority of the decomposition took place in the calcination step, which consisted of a burning segment where the hydrocarbon chain decomposes, a sulfur removal segment that was assisted by a change in purge gas, and then an oxidation period [1,7]. These transitions are not precise and depend upon the heating conditions.…”
Section: Decompostionmentioning
confidence: 99%
See 3 more Smart Citations